Quality Function Deployment and Design Risk Analysis for the Selection and Improvement of FDM 3D Printer. Issue 6 (March 2021) - Zagidullin, R; Mitroshkina, T; Dmitriev, A
Abstract: Currently, the use of additive technologies is becoming relevant instead of traditional production technologies. The market offers a fairly large selection of 3D printers with different designs and kinematics. Each design and kinematics has its own disadvantages and advantages. The article demonstrates various versions of the kinematics of FDM 3D printers, the main units and parts, as well as their impact on the quality of 3D printing of parts. The results of structuring the quality function (QFD) and analysis of the types and consequences of potential inconsistencies (FMEA) of an FDM 3D printer for prototyping and manufacturing parts and assemblies for unmanned aerial vehicles are presented. A qualimetric assessment of the quality of FDM 3D printers with various kinematics design based on the QFD interconnection matrix was carried out. The aim of the study is to analyze the design and kinematics of FDM 3D printers for the manufacture of high-quality parts and assemblies for unmanned aerial vehicles without further post-processing based on the application of the QFD methodology. Based on the results of the study, recommendations and proposals for improving the design of FDM 3D printers were developed.